Determinan Nilai Perusahaan Dengan Struktur Modal Sebagai Variabel Moderating Pada Perusahaan Industri Sektor Consumer Goods Bursa Efek Indonesia - Putri, Wulan Wahyuni Rossa; Tartilla, Nilda; Sutomo, Hadi; Yuliandi, Yuliandi (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to examine and analyze the determinants of firm value with capital structure as a moderating variable, how do the effects of Return On Assets (ROA), Debt Equity Ratio (DER), Debt Asset Ratio (DAR), DAR can moderate ROA and DER in influencing firm value . This research approach employs a descriptive methodology, which involves describing and analyzing research findings without drawing broader conclusions. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) with the consumer goods sector. The sample was determined using purposive sampling method. The analytical method used in this study is multiple regression with the SPSS version 25 program and hypothesis testing is carried out using the moderate regression analysis (MRA) method. The results showed that partially ROE had a positive effect on firm value with a significance value of 0.000, while DER had no negative effect on firm value with a significance value of 0.803. DAR has no effect on firm value with a significance value of 0.156 and capital structure (DAR) can strengthen profitability (ROE) in influencing firm value with a significance value of 0.005. Meanwhile, capital structure (DAR) cannot strengthen Solvability (DER) in influencing firm value. Simultaneously ROA, DER, DAR can affect company value in consumer goods listed on the Indonesia Stock Exchange. The limitations of this study are the limitations of the processed data and the limitations of the variables used. Hopefully this research can be useful for the community, especially investors or investors as a material consideration in investing in companies Keywords: ROA, DER, DAR, ROE